Pain Management and the Primary Care Encounter - Meghan Gannon MSPH; Amir Qaseem MD, PhD, MHA, FACP; Vincenza Snow MD, FACP; Qianna Snooks BA (SAGE Publishing, 2011)
Purpose: The purpose of this pilot study was to create a comprehensive pain management educational toolkit for the primary care physician that offers guidance on current standards of care and quality improvement techniques to help curb educational and quality gaps in managing patients with pain. Scope: Pain often goes undetected in the primary care encounter, and when acknowledged, is often undertreated. Methods: This pilot study utilized a pre-/postintervention design. Data were collected using a unique survey developed for this project. The intervention consisted of an online educational toolkit designed to improve the quality of care primary care physicians offer their patients with pain. Results: Results demonstrated statistically significant improvements from pre- to postintervention for various measures including the following: (1) reported comfort in managing patients with cancer and fibromyalgia; (2) number of physicians who set functional goals for patients with pain; (3) screening for depression, substance abuse, and alcoholism; (4) documentation of efficacy of nonpharmacologic modalities; and (5) knowledge scores. Conclusion: The improvements seen from pre- to postintervention suggest the online toolkit had a positive impact on physician knowledge, practice patterns, and behavior toward pain management.